1999
DOI: 10.1038/sj.bmt.1701594
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus infection associated with high-dose chemotherapy and autologous stem-cell rescue

Abstract: Summary:A retrospective evaluation of 215 consecutive recipients of high-dose chemotherapy (HDC) and autologous stem cell rescue (ASCR) was conducted to ascertain the incidence, temporal course, and outcome of varicella zoster virus (VZV) infection. Herpes zoster was identified in 40 individuals at a median of 69 days following ASCR. Six of these cases occurred at a median of 33 days prior to ASCR but following the initiation of high doses of stem cell mobilization chemotherapy. Twenty-five percent of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 10 publications
3
38
2
6
Order By: Relevance
“…There were 10 cases of chickenpox, 43 of typical herpes zoster infection and seven disseminated zoster infections. 8 Similar results were published recently by Bilgrami et al 9 Moreover, in a large review of 1394 patients who received allogeneic or syngeneic bone marrow transplantation, Locksley et al 10 found allogeneic transplantation, GVHD and treatment with antithymocyte globulin-independent risk factors for VZV infection. In their cohort 80% of infections occurred within the first 9 month after transplant.…”
Section: Discussionsupporting
confidence: 73%
“…There were 10 cases of chickenpox, 43 of typical herpes zoster infection and seven disseminated zoster infections. 8 Similar results were published recently by Bilgrami et al 9 Moreover, in a large review of 1394 patients who received allogeneic or syngeneic bone marrow transplantation, Locksley et al 10 found allogeneic transplantation, GVHD and treatment with antithymocyte globulin-independent risk factors for VZV infection. In their cohort 80% of infections occurred within the first 9 month after transplant.…”
Section: Discussionsupporting
confidence: 73%
“…Patients who underwent an allogeneic HSCT had a significantly higher risk of HZ infection than patients who received an autologous HSCT, presumably due to the greater pharmacologic and allogeneic-mediated immune suppression. 12,26,27 Among allogeneic HSCT recipients, conditioning with TBI approached significance as a risk factor when compared to conditioning with chemotherapy alone. 4,28 However, patients who had underlying immunodeficiency or chemotherapy prior to HSCT did not demonstrate a greater risk of HZ infection compared with those presumed less compromised prior to HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…antiviral therapy, and, despite treatment, had an incidence of complications that parallels rates described in several adult studies. 1,13,26 Of 64 patients, 58 (91%) of the cohort with HZ reactivation were hospitalized to receive i.v. acyclovir.…”
Section: Discussionmentioning
confidence: 99%
“…HZ is common after allogeneic or autologous BM or peripheral blood hematopoietic SCT. [4][5][6][7][8][9][10][11][12][13][14][15][16] The incidence of HZ at 1 year following autologous SCT (ASCT) varies from 8 to 30%. 3,11,[14][15][16] However, little is known about the incidence of HZ specifically in myeloma patients undergoing ASCT.…”
Section: Introductionmentioning
confidence: 99%